Understanding innovation diffusion attributes towards internet tv adoption in enhancing students learning experience / Dzaa Imma Abdul Latiff... [et al.] - Abdul Latiff, Dzaa Imma; Yaassin, Megat Al-Imran; Ridzuan, Abdul Rauf; Ramli, Noryusnita; Sultan Mohideen, Rosilawati; Ab Ghani, Siti Nur Farrah Faadiah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
The entertainment technology nowadays such as Internet TV has become an excellent medium in creating awareness on news and current issues to public especially to the students. The expensive cost of technology might contribute to barriers of integrated to higher learning. Internet TV in Malaysia is relatively new and most studies are mainly focused on business and technology impact. This paper studied about innovations attributes towards Internet TV adoption to enhance students learning experience. A modified framework of Innovation of Diffusion theory was used to explore the exogenous variables that influenced students to adopt. 352 respondents were selected among the undergraduate students which were later analyzed through covariance-based structural equation modelling. The findings supported the notion that innovation attributes, except for trialability, give impact to students’ intention to use Internet TV for educational purposes. The results also improve our knowledge and understanding in a mission to inform that Internet TV as part of educational approach in teaching and learning. In conclusion, Innovation and Diffusion theory is a good theoretical medium to understand students’ intention to adopt Internet TV news. It is both beneficial and important for the researchers, educators, media practitioners and public.